PENDAMPINGAN DALAM MENINGKATKAN KEMAMPUAN PUBLIC SPEAKING SANTRI DI PONDOK PESANTREN MAMBA’UL HUDA KALIABU - Muhammad Afif Ma’ruf; Purwanto Purwanto (khidmatan, 2021)
Mamba'ul Huda Kaliabu Islamic Boarding School is one of the pesantren that is required to produce quality students in this field. Santri must be able to become a good public speaker when he or she has mingled with the community. The problem faced by some students is that students still have difficulty speaking well in public. There are many reasons behind this, including lack of confidence and lack of communication skills. The purpose of this service is to observe and assist and find out how the methods used by the students in learning to improve their public speaking skills. Due to the object of this dedication to religious education institutions, the practice of learning through Khitobah is carried out every Sunday night according to the schedule of the pesantren agenda. The approach used in this service is PAR (Participation Action Research). The method used in this service is training. Practically, the service carried out can help improve the public speaking skills of the Mamba'ul Huda Kaliabu Islamic Boarding School students.